Biosorption of lead from acid solution using chitosan as a supporting material for spore forming-fungal biomass encapsulation - Lang W. (2014)
Asexual spores of the filamentous fungus Rhizopus arrhizus were used as the resting biomass as they tolerate chitosan gelling for mycelia growing in chitosan beads. Biosorption of lead using the dead detergent pre-treated chitosan-immobilised and grown fungal beads was performed with initial lead (II) nitrate concentrations ranging from 9. 02 to 281. 65 mg/L. The adsorption data were best correlated with equilibrium adsorption isotherms in the order Redlich-Peterson, Langmuir, Freundlich and Fritz-Schlünder by non-linear regression. The biosorption kinetic model of pseudo second-order (R2 > 0. 99) fitted better than pseudo first-order and modified pseudo first-order models. Among the four pseudo second-order kinetic models, the Blanchard model was the best fit for the experimental biosorption data. The rate-limiting step of biosorption of lead was shown to be intraparticle diffusion controlled according to Weber and Morris model fitting. The beads could be regenerated using 1 M nitric acid solution. This illustrated the good performance of the beads for regenerated sorption/desorption at least five cycles. © 2013 CEERS, IAU.